Cooperative Assembly of CYK-4/MgcRacGAP and ZEN-4/MKLP1 to Form the Centralspindlin Complex - Pavicic-Kaltenbrunner, Visnja (The American Society for Cell Biology, 2007)
Cytokinesis in metazoan cells requires a set of antiparallel microtubules that become bundled upon anaphase onset to form a structure known as the central spindle. Bundling of these microtubules requires a protein complex, centralspindlin, that consists of the CYK-4/MgcRacGAP Rho-family GTPase-activating protein and the ZEN-4/MKLP1 kinesin-6 motor protein. Centralspindlin, but not its individual subunits, is sufficient to bundle microtubules in vitro. Here, we present a biochemical and genetic dissection of centralspindlin. We show that each of the two subunits of centralspindlin dimerize via a parallel coiled coil. The two homodimers assemble into a high-affinity heterotetrameric complex by virtue of two low-affinity interactions. Conditional mutations in the regions that mediate complex assembly can be readily suppressed by numerous second site mutations in the interacting regions. This unexpected plasticity explains the lack of primary sequence conservation of the regions critical for this essential protein–protein interaction.